REDUKSI FUNGSI ANGGARAN DPR DALAM KERANGKA CHECKS AND BALANCES - Yutirsa Yunus; Reza Faraby (Jurnal Yudisial, 2014)
ABSTRAKPutusan Mahkamah Konstitusi Nomor 35/PUU-XI/2013 merupakan salah satu putusan penting. Putusan ini telah merombak struktur ketatanegaraan Indonesia yang menyimpang dari prinsip-prinsip negara hukum demokratis, khususnya dalam pelaksanaan fungsi anggaran oleh pemerintah dan DPR. Kewenangan dua lembaga dalam melaksanakan fungsi perencanaan dan penganggaran pada dasarnya merupakan konsekuensi konsep negara hukum yang menganut prinsip checks and balances, yang bertujuan agar kekuasaan tidak hanya terletak pada satu tangan dan menghasilkan sistem pemerintahan yang korup dan otoriter. Namun, pelaksanaan fungsi anggaran oleh kedua lembaga harus memerhatikan batasan-batasan sesuai fungsi masing-masing agar tidak terjadi intervensi domain kekuasaan, konflik horizontal, maupun penyalahgunaan kekuasaan. Dalam hal ini, putusan Mahkamah Konstitusi Nomor 35/PUU-XI/2013 berhasil membatasi kewenangan DPR dalam membahas R-APBN hanya sampai pada tingkat program. Pembatasan fungsi DPR ini merupakan upaya tepat agar DPR tidak menjadi sewenang-wenang dan justru mengacaukan sistem perencanaan dan penganggaran Pemerintah RI. Dengan demikian, putusan ini telah mereposisi kembali fungsi checks and balances di mana pemerintah mewujudkan fungsi perencanaan pembangunan dan penganggaran, sementara DPR mewujudkan fungsi politik anggaran yang sesuai amanat UUD NRI 1945.Kata kunci: fungsi anggaran, APBN, checks and balances.ABSTRACTThe Constitutional Court Decision Number 35/PUU-XI/2013 is one of the crucial decisions. This decision has revolutionized the Indonesian constitutional structure which seems to have deviated from democratic principles and rule of law, especially in the implementation of budgeting function by the government and the parliament. Those two agencies’ authorities in carrying out the function of planning and budgeting are basically a consequence of checks and balances principle in the rule of law, which aims to prevent corruption and authoritarian system resulted from an absolute government power. However, the implementation of the budgeting function by both agencies should give attention to each agency’s function limits in order to avoid intervention of power, conflict of interest, and abuse of power. In this case, the Constitutional Court Decision No. 35/PUU-XI/2013 has affirmed the limitation to the Parliament’s authority to discuss the National Budget Plans only in the scheme level. This limitation of the functions of Parliament is made as an effort to prevent the Parliament’s authority being that could possibly disrupt the government’s planning and budgeting system. Thus, this decision has repositioned the function of checks and balances, in which the government holds the function of development planning and budgeting, while the House of Representatives implements the budgeting policy as mandated on the 1945 Constitution of the Republic of Indonesia.Keywords: budgeting function, the National Budget Plans, checks and balances.